Dairy goats fed sunflower hay intercropped with chickpea in small-scale systems. Part II: Cheese yield and composition, sensory analysis and economic performance - Sainz-Ramírez, Aurora; Estrada-Flores, Julieta-Gertrudis; Velarde-Guillén, José; López-González, Felipe; Arriaga-Jordán, Carlos-Manuel (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Goat production has grown worldwide as a way to improve the quality of rural life and reduce the environmental footprint; nevertheless, there is a need to increase productivity through improved feeding strategies. The market demands healthier products with organoleptic characteristics similar to the traditional ones; thus, it is necessary to evaluate the effect of new forages for goats and its acceptance by consumers. Chemical and organoleptic composition of goat milk vary according to the diet which, in turn, affects the characteristics of cheese. Cheese texture, taste and smell are the most important sensory attributes for consumers. Objective: To evaluate the effect of substituting corn straw with sunflower hay associated with chickpea for dairy goats on yield, chemical composition and sensory acceptability of cheese, as well profitability. Methods: Twenty-eight Saanen dairy goats were randomly assigned to two treatments in a 30-day experiment on a small farm. The daily ration per goat in the MZST treatment (control treatment) consisted of alfalfa hay (200 g/goat/day) and concentrate (400 g/goat/day) plus 600 g/goat/day (50% of the ration) of corn straw. The SFCP treatment substituted corn straw with sunflower-chickpea hay; it had the same alfalfa and concentrate content, but with no corn straw and was added with 600 g/goat/day of sunflower-chickpea hay. The yield, composition and sensory evaluation of fresh cheese made with milk from each treatment were recorded, and the feeding costs and returns evaluated. Variables for the chemical composition of cheese were analyzed following a completely randomized design. Results: Significant differences were observed in cheese yield and all chemical composition variables. According to sensory evaluation, SFCP cheese had significantly higher scores for texture and odor but lower for taste and overall acceptability compared to MZST. In terms of profitability, SFCP increased feed costs by 5% but resulted in higher margins over feed costs of 12 and 24% for milk and cheese, respectively, compared to MZST. Conclusion: In spite of favorable performance and economic returns of MZST treatment (control treatment), the organoleptic characteristics of the cheese reduced its general acceptance.